Ecological Restoration Assessment Based on the PSRS Model: A Case Study of Huangshui National Wetland Park - Liu, Xiaojun; Mao, Xufeng; Wei, Xiaoyan; Tao, Yaqin; Zhang, Zhifa; Chen, Yupeng; Su, Xiaoxia; Zhang, Shuai (Journal of Environmental Accounting and Management, 2026)
Effectiveness evaluation is a fundamental basis for implementing and managing wetland restoration projects. A case study was conducted in the Huangshui National Wetland Park (HNWP) in Qinghai Province to evaluate the effectiveness of the restoration project there. First, a Pressure-State-Response-Services (PSRS) model system to evaluate effectiveness was created. This consisted of 19 indicators, grouped into four broad categories: Pressure, State, Response and Services. Data for 2012 and 2016 were obtained by field investigation, lab tests, questionnaire surveys, and historical data analysis. Weights of these indicators were determined by implementing the analytic hierarchy process (AHP) and consulting experts. The comprehensive health index (CHI) and restoration effectiveness (RE) were developed to allow for time-specific and region-specific evaluations of wetland restoration programme effectiveness. The results show that the restoration project has improved the health status of the HNWP: the park’s overall CHI increased from 0.319 in 2012 to 0.620 in 2016, representing a RE of 0.301. Spatial and temporal variability in the park’s CHI was observed. Spatially, the CHI values of the Haihu Wetland (region A), Xigang Wetland (region B), Huoshaogou Wetland (region C), and Ninghu Wetland (region D) were 0.629, 0.62, 0.576, and 0.581, respectively, suggesting that regions A and B were in good health while regions C and D were in fair health. In the warm season, the CHI of regions A, B, C, and D were 0.702, 0.685, 0.624, and 0.629, respectively, indicating overall good health. In the cold season, their CHI declined to 0.557, 0.555, 0.527, and 0.533, respectively, indicating fair health. A sensitivity analysis reveals that the PSRS model proposed has good applicability and is sensitive to changes in State and Services indicators. The findings of this case study are expected to provide a reference for future wetland restoration and conservation projects in Qinghai.